2021
DOI: 10.3390/gels7030129
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation and Theoretical Analysis of Slide-Ring Gels under Biaxial Deformation

Abstract: Slide-ring (SR) gels, a new type of gels that have cross-links moving along the chains, are known to have unique mechanical characteristics. In the case of biaxial deformations, it has been experimentally shown that the stress–strain (S–S) relationships of SR gels can be well described by the neo-Hookean (NH) model. This behavior is quite different from that of conventional chemical gels, where the S–S curves deviate from the NH model. To understand the molecular mechanism of such peculiar elastic properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…27 With the introduction of the alignment entropy of uncross-linked rings between crosslinks, a finite Young's modulus of slide-ring gels was predicted, 27 which, unfortunately, did not quantitatively agree with the value reported in experiments. Molecular dynamics simulations for relatively small stretch under different loading conditions were also performed, 28,29 based on which a simple equation for the Young's modulus as a function of degree of sliding of crosslinks was developed. 29 It was suggested that movable crosslinks could explain the elasticity of slide-ring gels by suppressing the nonlinear stretch of polymer chains 28 and also overcome the trade-off relationship between the stiffness and toughness of polymer network within slide-ring gels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 With the introduction of the alignment entropy of uncross-linked rings between crosslinks, a finite Young's modulus of slide-ring gels was predicted, 27 which, unfortunately, did not quantitatively agree with the value reported in experiments. Molecular dynamics simulations for relatively small stretch under different loading conditions were also performed, 28,29 based on which a simple equation for the Young's modulus as a function of degree of sliding of crosslinks was developed. 29 It was suggested that movable crosslinks could explain the elasticity of slide-ring gels by suppressing the nonlinear stretch of polymer chains 28 and also overcome the trade-off relationship between the stiffness and toughness of polymer network within slide-ring gels.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics simulations for relatively small stretch under different loading conditions were also performed, 28,29 based on which a simple equation for the Young's modulus as a function of degree of sliding of crosslinks was developed. 29 It was suggested that movable crosslinks could explain the elasticity of slide-ring gels by suppressing the nonlinear stretch of polymer chains 28 and also overcome the trade-off relationship between the stiffness and toughness of polymer network within slide-ring gels. 30 As revealed in experiments, the crack resistance of slide-ring gels was sensitive to the strain rate and the measured fracture energy of slide-ring gels decreased dramatically around a strain rate of 0.2/s.…”
Section: Introductionmentioning
confidence: 99%